PERLINDUNGAN HUKUM TERKAIT EKPRESI BUDAYA TRADISIONAL “LAGU TRADISIONAL ACEH” DALAM BINGKAI HAK CIPTA - Nugraha, Tyas Adi Putra (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Traditional Cultural Expression is an intellectual work that needs to be protected. Traditional Cultural Expression is rooted in three words: tradition, culture, and expression. The meaning of "expression", expresses a clear goal, idea or feeling. In this paper, the author raises an example of a traditional cultural expression, namely the cultural expression of traditional Acehnese songs owned by the local Acehnese people. Songs such as "Bungong Jempa", are a small example of the traditional wealth of the Acehnese people that should be preserved and protected by the government. The purpose of this study is to find out how is the protection related to traditional cultural expressions in Indonesia? And has the method of recording/inventorying traditional cultural expressions in Indonesia provided maximum protection for the cultural expressions of traditional Acehnese songs? The benefit of this research is that it is hoped that it can provide benefits for the development of legal knowledge in Indonesia and can provide insight or information to the public, especially regarding the object of copyright as one of the productive waqf in Indonesia.